2009
DOI: 10.1083/jcb.200902101
|View full text |Cite
|
Sign up to set email alerts
|

A ZYG-12–dynein interaction at the nuclear envelope defines cytoskeletal architecture in the C. elegans gonad

Abstract: Changes in cellular microtubule organization often accompany developmental progression. In the Caenorhabditis elegans embryo, the centrosome, which is attached to the nucleus via ZYG-12, organizes the microtubule network. In this study, we investigate ZYG-12 function and microtubule organization before embryo formation in the gonad. Surprisingly, ZYG-12 is dispensable for centrosome attachment in the germline. However, ZYG-12–mediated recruitment of dynein to the nuclear envelope is required to maintain microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 38 publications
7
103
0
Order By: Relevance
“…Therefore, the peripheral nuclei experience spatial constraints. However, when zyg-12 is mutated, the resulting nuclei become randomly distributed, and an increased nuclear size can be observed (Zhou et al, 2009). According to our model, this can be explained by releasing the spatial constraint and enabling the generation of a larger MT-occupied space.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, the peripheral nuclei experience spatial constraints. However, when zyg-12 is mutated, the resulting nuclei become randomly distributed, and an increased nuclear size can be observed (Zhou et al, 2009). According to our model, this can be explained by releasing the spatial constraint and enabling the generation of a larger MT-occupied space.…”
Section: Discussionmentioning
confidence: 82%
“…Contrary to this, if the nucleus is located in the periphery of the cell, then the MT-occupied space cannot expand freely because of the spatial limitation imposed by the cell membrane. This hypothesis is supported by in vivo data from large cells; in the C. elegans syncytium gonad, the nuclei are anchored to the plasma membrane by interaction of ZYG-12 on the nuclear membrane with MTs emanating from the plasma membrane (Zhou et al, 2009). Therefore, the peripheral nuclei experience spatial constraints.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, reduction of the surface area of the NE or prevention of NE assembly causes centrosomes to separate prematurely, further demonstrating the importance of the NE in centrosome positioning (Askjaer et al 2002;Meyerzon et al 2009b). SUN-1/ZYG-12 activity is also required for nuclear tethering to centrosomes in embryos beyond the one-cell stage (Penkner et al 2007) and for connection of syncytial germ line nuclei to the microtubule cytoskeleton (Zhou et al 2009). Recently, delay in nuclear separation and centrosome detachment was also observed in lem-2-mutant two to four cell-stage embryos ( Figure 16A) (Morales-Martinez et al 2015), but it remains to be analyzed if this phenotype reflects an interaction of LEM-2 with the LINC complex or an alternative anchoring mechanism.…”
Section: Nuclear Migration and Positioningmentioning
confidence: 99%
“…In various studies on non-muscular cells, nesprins have been implied to interact with the actin cytoskeleton (Starr and Han, 2002;Zhen et al, 2002;Padmakumar et al, 2004). In addition, nesprins and related proteins have been shown to interact with components of the microtubule network, such as kinesin, dynein and dynactin, and with the centrosome (Malone et al, 2003;Roux et al, 2009;Zhang et al, 2009;Zhou et al, 2009;Fridolfsson et al, 2010;Yu et al, 2011;Holzbaur, 2012, 2015). Several groups have reported that proteins of the centrosome, such as PCM-1, pericentrin and γ-tubulin, are relocated from the pericentriolar material to the nuclear envelope upon onset of myoblast differentiation, and that a substantial amount of microtubules grow from the nuclear surface following this reorganization (Tassin et al, 1985a;Bugnard et al, 2005;Srsen et al, 2009;Fant et al, 2009).…”
Section: Introductionmentioning
confidence: 99%